Upaya Peningkatan Intensi Perilaku Hidup Bersih dan Sehat pada Siswa SDN 01 Muaro Paiti - Aria Gusti; Teta Try Fatul; Fuadilla Alhumairah; Putri Magvira; Muhammad Iqbal (Warta Pengabdian Andalas, 2021)
The application of Clean and Healthy Living Behavior (PHBS) in the school environment is one of the strategic efforts to empower teachers and students to live clean and healthy in their surroundings. The PHBS itself need to be educated continuously in the community, especially when the Covid-19 is epidemic. State Elementary School 01 Muaro Paiti is located in Kapur IX sub-district, district of 50 Kota, West Sumatra, which can be an example for other schools implementing PHBS in school settings. Social education activities were begun by establishing communication with the principal to obtain permission from partners. In this initial communication, a discussion was held on what fundamental issues and received priority to find solutions to improve students' clean and healthy living behaviour at school and in their lives. The discussion results agreed that it was necessary to deliver materials and practices on clean and healthy living behaviour in school settings. The second activity was preparing PHBS learning materials and interactive media in the school. Preparation was carried out in discussions with teammates to determine materials and methods that are more efficient and effective in implementing learning in schools, i.e. that learning was given in the form of presentations and hands-on practice. The third activity was the implementation of PHBS learning in the school. Students and teachers were very enthusiastic about participating in this activity. It is hoped that students who become participants in PHBS learning in this prospected school can become role models for students and the environment in which they live.